2022
DOI: 10.48550/arxiv.2207.00077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breaking one into three: surface-tension-driven droplet breakup in T-junctions

Abstract: Droplet breakup is an important phenomenon in the field of microfluidics to generate daughter droplets. In this work, a novel breakup regime in the widely studied T-junction geometry is reported, where the pinch-off occurs laterally in the two outlet channels, leading to the formation of three daughter droplets, rather than at the center of the junction for conventional T-junctions which leads to two daughter droplets. It is demonstrated that this new mechanism is driven by surface tension, and a design rule f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In this paper, we presented an extremely simple method for deterministic single-cell encapsulation in droplets. Based on a newly discovered droplet instability, 34 we developed an automatic workflow using a cell triggered splitting phenomenon (CTS) to create smaller satellite droplets containing single cells, for downstream separation of the positive droplets. Also for the post-encapsulation droplet size-based sorting, Chabert et al 40 reported a different mechanism for inducing droplet size difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we presented an extremely simple method for deterministic single-cell encapsulation in droplets. Based on a newly discovered droplet instability, 34 we developed an automatic workflow using a cell triggered splitting phenomenon (CTS) to create smaller satellite droplets containing single cells, for downstream separation of the positive droplets. Also for the post-encapsulation droplet size-based sorting, Chabert et al 40 reported a different mechanism for inducing droplet size difference.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method is based on a recent observation of a new droplet splitting instability in microfluidic T junctions. 34 Due to this splitting instability that occurs naturally in microfluidic junctions of specific geometries, a concept of cell-triggered splitting (CTS) is developed to achieve the passive and deterministic single-cell encapsulation in droplets without synchronization. A high throughput, labelfree, cost-effective, and robust single-cell encapsulation method will be demonstrated in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…At the start, a random cell encapsulation is performed using a standard flow focusing geometry with low cell density (λ = 0.1 − 0.2), producing mother droplets that are mostly empty or contain a single cell [12]. These droplets then flow through a T junction designed to implement droplet splitting instability conditions [34]. In this T junction, empty mother droplets are split in two, but mother droplets containing a cell induce a lateral splitting instability as described in [34], which creates one additional small satellite droplet containing the cell.…”
Section: Concept Of Cell Triggered Splitting System (Cts) For Single ...mentioning
confidence: 99%
“…These droplets then flow through a T junction designed to implement droplet splitting instability conditions [34]. In this T junction, empty mother droplets are split in two, but mother droplets containing a cell induce a lateral splitting instability as described in [34], which creates one additional small satellite droplet containing the cell. As a result, two types of droplets are obtained after splitting: large empty droplets and small cell-loaded satellite droplets.…”
Section: Concept Of Cell Triggered Splitting System (Cts) For Single ...mentioning
confidence: 99%
See 1 more Smart Citation